The size of Wiman–Valiron discs for subharmonic functions of a certain type. Issue 4 (2nd April 2016) - Fenton, P.C.; Lingham, E.F.
Abstract : Wiman–Valiron theory and the results of Macintyre about "flat regions" describe the asymptotic behaviour of entire functions in certain discs around maximum points. We use a technique of Bergweiler, Rippon and Stallard to describe the asymptotic behaviour of a certain type of subharmonic function, and a technique of Bergweiler to estimate the size of its Wiman–Valiron discs from above and below. The results are extended to -subharmonic functions.